1978
DOI: 10.1111/j.2044-8341.1978.tb02468.x
|View full text |Cite
|
Sign up to set email alerts
|

Failure to mourn a stillbirth: An overlooked catastrophe

Abstract: The reasons for the difficulty of mourning a stillbirth and the therapeutic management of this mourning process are outlined. A case is described of failed mourning of a stillbirth which gave rise to a profound disturbance in mothering of a subsequent live baby. A psychotherapeutic technique is discussed which facilitates the failed mourning of a stillbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0
3

Year Published

1984
1984
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(42 citation statements)
references
References 2 publications
1
38
0
3
Order By: Relevance
“…For a number of reasons, the mourning that follows perinatal losses is distinct from mourning following other losses (Benfield, Leib, & Vollman, 1978;Kirkley-Best & Kellner, 1982;Leon 1992;Parkes, 1965;Theut, Pedersen, Zaslow, & Rabinovich, 1988;Theut, Zaslow, Rabinovich, Bartko, & Morihisa, 1990;Toedter, Lasker, & Alhadeff, 1988;Zeanah, 1989). First, perinatal loss not only violates a mother's expectations, it also effects her perception of her own reproductive efficacy and ability to parent (Lewis & Page, 1978;Leon, 1992). Second, many potentially supportive people may regard perinatal loss as less important or less meaningful than losses of other kinds (Danis & Zeanah, 1991).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…For a number of reasons, the mourning that follows perinatal losses is distinct from mourning following other losses (Benfield, Leib, & Vollman, 1978;Kirkley-Best & Kellner, 1982;Leon 1992;Parkes, 1965;Theut, Pedersen, Zaslow, & Rabinovich, 1988;Theut, Zaslow, Rabinovich, Bartko, & Morihisa, 1990;Toedter, Lasker, & Alhadeff, 1988;Zeanah, 1989). First, perinatal loss not only violates a mother's expectations, it also effects her perception of her own reproductive efficacy and ability to parent (Lewis & Page, 1978;Leon, 1992). Second, many potentially supportive people may regard perinatal loss as less important or less meaningful than losses of other kinds (Danis & Zeanah, 1991).…”
mentioning
confidence: 93%
“…Second, many potentially supportive people may regard perinatal loss as less important or less meaningful than losses of other kinds (Danis & Zeanah, 1991). Third, is has been found that healthy resolution of mourning following perinatal loss is more difficult than that following other losses because of the paucity of memories available to adults whose infant dies (Kennell & Trause, 1978;Lewis, 1979;Lewis & Page, 1978). Memories facilitate the process of mourning, but following the death of a newborn, there is so little for mothers to remember that it may be difficult for them to resolve the loss.…”
mentioning
confidence: 95%
“…Either way, some of the issues discussed in the workbook could be interpreted as psychologically provocative, whether or not the learner has encountered a perinatal loss at a professional or personal level. The following student acknowledges this affect: Parents declining opportunity to hold their deceased infant may affect the course of grieving in unproductive ways (Lewis, 1976(Lewis, , 1979, with evidence embedded in clinical accounts of parents treated for psychological problems post stillbirth (Lewis, 1978;Bourne & Lewis, 1984). In response, an eruption of papers, books, and seminars espousing necessity for parent/infant contact post stillbirth now underpin bereavement protocols in the UK maternity units (e.g., Kelly, 2007;Mander, 2006;SANDS, 2009 …”
Section: The Workbook Helped You To Understand the Grief Process And mentioning
confidence: 99%
“…Moreover, the subsequent child is idealized in a way which could be regarded as a maladaptive behavior, one of the key signs of masked grief [43]. In two studies the "replacement child syndrome" is used as a possible indicator of pathological grief [60,61]. In these studies an over-idealization of the dead infant and not seeing the subsequent child as a separate individual are used as key signs of pathological grief.…”
Section: Defining and Assessing Pathological Grief Following Pregnancmentioning
confidence: 99%